Functional vision in daily life: Clinical and patient-reported outcomes 18 months after enhanced partial range of field IOL implantation - Catharina Latz; Annika Licht; Katharina A. Ponto; Johannes Menzel-Severing; David P. Piñero; Alireza Mirshahi (PLoS ONE, 2025)
Background Partial range of field (PROF) intraocular lenses (IOLs) provide good distance visual acuity with enhanced intermediate visual acuity. Neuroadaptation to new intraocular lenses can take several months. This study investigates visual and patient-reported outcomes (PROMs) in patients implanted with the PROF IOL ICB00 (Johnson & Johnson Vision) 18 months post-surgery. A particular focus was put on spectacle independence while performing activities of daily life. Methods This ambispective, single-center study included 41 patients (aged 48–84). Visual acuities (distance, intermediate), refraction, and PROMs were assessed ≥18 months post-surgery. Spectacle independence was evaluated using the PRSIQ questionnaire. Patients also self-reported on visual quality, task performance, and photic phenomena. Results Binocular visual acuity of 0.20 logMAR or better was achieved by 100.0% of patients for uncorrected or corrected distance, by 73.2% for uncorrected intermediate, and by 79.5% for distance-corrected intermediate vision. Photic phenomena were reported by <10%. Mean visual quality scores were 1.68 ± 0.72 for distance and 2.05 ± 0.92 for intermediate vision, where 1 equaled very good and 6 equaled very poor. Complete spectacle independence was reported by 87.8% for distance and 53.7% for intermediate vision. Satisfaction rates were 90.2% (distance), 87.8% (intermediate), and 51.2% (near). Conclusions The ICB00 IOL provides excellent long-term distance and satisfactory intermediate vision, with high spectacle independence and even higher patient satisfaction, although most patients require spectacles for near vision. Trial registration This study was approved by the medical ethics committee of the Medical Chamber of North-Rhine, Germany (CE # 2124770CE01).